[AR] Al-Alghaz al-Nahwiyyah fi ba’d al-Mu’allafat al-‘Arabiyyah fi l-Diyar Nigeria: Kitab “Rawa’i’ al-Hikam fi Bada’i’ al-Kalim” li Umar Muhammad al-Awwal al-Imam Unmuzajan: Arabic Syntactical Puzzle in some Arabic Books Authored in Nigeria: The Book "Rawa’i’ al-Hikam fi Bada’i’ al-Kalim" by Umar Muhammad al-Awwal al-Imam as a Case Study (Afaq Lughawiyyah, 2024)
This research in its arena aims towards mentioning something with a particular adjective, purposely because of the relationship between that adjective and the content itself, to achieve clarity meaning, as it contained a rapport and similarity between the object meanings of an applied word, with the actual motive of an intended meaning. Verily, the Symantec's metaphor is emerged useful direction and needful intervention to elaborate and analyze artistic of Syntactical Puzzle in some Arabic books authored in Nigeria. The problem of research emphasized on an indicative structure of artistic in different peak of stylistic decorations with some secrets behind it, as this work engaged not neglecting their semantic purposes and linguistic characteristics that fully installed and perfectly used by the author of  the book entitled: (Masterpiece of Wisdom in the Marvelous Expression), while arranging the resonant words to give attractive meanings of the bright ideas. This ranges from the splendor of eloquence, the quality of concept, the strength of meaning, and the strangeness of linguistic temper with multi-significance. The importance of this article is now imbibed in an analytical and applied methodology, heading towards the formation of the quality of the studious book and its relevance with the main topic of discussion, the researcher has maintained steadfastness as he deeply looked toward the Syntactical Puzzle in the chosen book as a case study, to point out great model, a flexible formulation and a charming tenderness, in derivation and composition, arrangement and depiction, as he is describing its evidence in an accurate description.